Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Motivasi Kerja yang Berdampak pada Kepuasan Kerja Karyawan di PT Balina Agung Perkasa (BAP) - Laurensius R.J.U.Y.S. (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The aim of this research is to explain the relationship and the influence of several variables that have been defined. Data analysis technique using Structural Equation Modeling (SEM) to describe the relationship with the indicator latent variables and for mengggambarkan relationships between latent variables. Distributing questionnaires conducted with purposive sampling method. The population sample of 155 respondents with 112 respondents specified. After testing and analyzing the data to test hypotheses proposed study, obtained some conclusions that organizational culture directly affects motivation and has no direct influence on job satisfaction. The leadership style directly affects the motivation and influence directly and indirectly to job satisfaction. The leadership style indirect direct effect on job satisfaction variables. Organizational culture, leadership and motivation to work simultaneously influence on job satisfaction.